Potato Physiological Disorders - Growth Cracks - Lincoln Zotarelli; Chad Hutchinson; Seth Byrd; Douglas Gergela; Diane L. Rowland (EDIS)
Growth cracking is an external noninfectious physiological disorder of the potato tuber in which the tuber splits while growing. The split heals but leaves a fissure in the tuber. Growth cracks generally start at the bud or apical end of the potato and can extend lengthwise. They vary in severity from a surface abrasion to a split through the tuber, depending on the stage of growth during which the initial cracking occurred. This revised 2-page fact sheet was written by L. Zotarelli, C. Hutchinson, S. Byrd, D. Gergela, and D. L. Rowland, and published by the UF Department of Horticultural Sciences, May 2012.